Fearlessness about death and suicide planning predict lethality of adolescent suicide attempts during and following treatment. Issue 7 (3rd February 2022) - Krantz, Savannah M.; Heerschap, Jessica; Balzen, Kennedy M.; Sachs, Raney; Kennard, Betsy D.; Emslie, Graham J.; Stewart, Sunita M.
Abstract: Introduction: The rate of adolescent suicide attempt has increased drastically over the past 10 years. However, little is known regarding what predicts a more versus less lethal attempt, which is of critical interest to clinicians managing this at‐risk population. We sought to extend the study of lethality in adolescents by exploring its relationship with two recognized risk‐factors for suicide attempt: fearlessness about death (FAD) and suicide planning. Methods: Participants ( N = 254) were administered measures of FAD and depressive symptoms upon entering intensive outpatient treatment for adolescents exhibiting suicidal thoughts and behaviors. Attempts made between treatment entry and 6 months following discharge ( n = 47) were scored on a 4‐point ordinal scale of lethality. The resulting continuum ranged from no attempt to attempts of low to moderate levels of lethality. Results: FAD and suicide planning distinguished between levels of lethality of future attempt at the bivariate and multivariate level. FAD's predictive relationship with lethality while controlling for age, sex, depression, and prior attempt diminished when suicide planning was covaried. Conclusion: FAD and suicide planning significantly predicted more versus less lethal future attempts in our sample of adolescents in a clinical setting. Our findings suggest that FAD influences the lethality of a future attempt by promoting planning for suicide. More studies are needed to assess whether the brief FAD scale might be a valuable adjunct in the clinical management of youth with suicidal thoughts and behaviors.